Fentanyl Patches Usage in Children; Inappropriate Use May Be Death - Ayşegül Alpcan; Serkan Tursun; Ozan Ürem; Ümit Ayşe Tandırcıoğlu; Gülçin Aydın; Didem Aliefendioğlu (Galenos Yayinevi, 2020)
The use of transdermal fentanyl has increased in recent years, especially in patients with chronic pain. However, inappropriate use may have serious consequences. Here, we present a 10-year-old male patient who was admitted to the emergency department with respiratory arrest and exposed to inappropriate use of fentanyl patch.